PERBEDAAN HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN JARINGAN KOMPUTER FUNDAMENTAL YANG MENERAPKAN PEMBELAJARAN THINK PAIR SHARE DAN KONVENSIONAL DI JURUSAN SISTEM JARINGAN DAN APLIKASI SMK NEGERI 2 DEPOK SLEMAN - Bachtiar, Edo Zulfan; Rochayati, Umi (Journal of Information Technology and Education (JITED), 2024)
This study examines the effectiveness of the Think Pair Share learning method in improving student learning outcomes in the fundamental computer networking subject at SMK Negeri 2 Depok Sleman. Initial observations revealed challenges in maintaining student interest and active participation, prompting the testing of the Think Pair Share method as a potential solution. Using a quantitative approach, this research involved 72 10th-grade students from the network and application department, divided into experimental and control groups. Data was collected through observations, documentation, and learning outcome tests, then analyzed using normality, homogeneity, and hypothesis tests with the help of IBM SPSS Statistics. The results showed a significant difference between the Think Pair Share method and conventional learning, with average learning outcomes of 83.28 for the experimental class and 79.11 for the control class. Statistical analysis yielded a t-count value of 2.251 > t-table 2.032, confirming the effectiveness of the Think Pair Share method in improving student learning outcomes in this subject.